The application of the joint stimulus control model in teaching complex receptive language to children with autism spectrum disorder - Raudeliūnaitė, Rita; Steponėnienė, Eglė (Special Education, 2018)
Lithuanian educators are still not adequately well prepared to teach children with autism spectrum disorder (further in text ASD). There is a lack of research, the access to evidence-based methods is limited, and traditional educational methodological approaches are usually ineffective (Diržytė, Mikulėnaitė, & Kalvaitis, 2016; Buivydaitė, Newman, & Prasauskienė, 2017).One of the earliest signs of ASD is failure to develop language and social communication (Mody & Belliveau, 2013; Arunachalam & Luyster 2016; etc.). Meta-analyses conducted by foreign researchers show that B.F. Skinner’s (1957) verbal behaviour analysis is one of the evidence-based effective methods used for developing language in children with ASD (McPherson et al., 1984; Dymond et al. 2006; Sautter & LeBlanc, 2006; Devine & Petursdottir, 2017). A rapid increase in the prevalence of ASD brings the researchers’ attention to the possibilities of applying this method, however, there are still some areas in verbal behaviour approach remaining, which lack research. Scientific studies in these areas would likely open effective ways for developing language in children with ASD (Devine & Petursdottir, 2017). The researchers (Buivydaitė, Newman, & Prasauskienė, 2017) have conducted a review of scientific articles on ASD in the Baltic states (including Lithuania), and the findings of it confirm the lack of such research.In this study, a single-subject educational experiment was used, during which a joint stimulus control model was applied for developing language in children with ASD, with the main focus being on receptive language acquisition. The object of joint stimulus control is the development of a symmetrical (bi-directional) word-object relation and independent, verbally maintained generalisation with unlearned stimuli. The results of the experiment show that a joint stimulus control model can be applied as an effective mechanism to develop language in children with ASD. In the presence of non-verbal stimuli and rehearsing the names of the stimuli overtly or covertly, the joint stimulus control emerges and, in this way, the complex receptive language perception in children with ASD is developed within the context of social interaction. The participants of this experiment were able to emit correct responses with the novel sets of stimuli and were able to apply this mechanism without prompts not only in teaching sessions, but also in other social situations.
Keywords: autism spectrum disorder; verbal behaviour; joint stimulus control; receptive language teaching; single subject educational experiment